FOLKTALE NARRATIVE TEXT LEARNING WITH JUDICATIVE CHARACTER BASED IN PRIMARY SCHOOL - Hendratno Hendratno (IAIN MADURA, 2017)
The learning of folklore texts, as a part of learning Indonesian language an literature in primary schools, should be adjusted to the learning theories which focus on contextual approach for the benefit students. Thus, learning literature in elementary school should be directed to good character buliding to develop the characteristics of primary school-aged children. The character building intended in this study is limited to judicative character such as being honest, disciplined, sensitive, and creative. The characteristics of folklore texts in the learning materials produced in this research were as follows (1) the popular folklore in the community, (2) the moral values content that educate the student in building judicative character, (3) folklore told in simple way, (4) the suitable folklore to be used in teaching the upper-class student, (5) using Indonesian Language, (6) not lecturing, (7) giving students a broad imaginative space.